Experimental evidence of the oxidation state through resonant Raman scattering - Valentinuzzi, Maria Cecilia (2008)
When atoms are irradiated by x-ray photons different kinds of interactions take place: the photn can be absorbed by the photoelectric effect or can suffer a Rayleigh or Compton scattering. However, under resonant conditions other low probability interactions can occur. One of these interactions is the resonant Raman scattering (RRS) [1]. The x-ray resonant Raman scattering is an inelastic process which presents fundamental differences compared to other scattering interactions between x-rays and atoms; when the energy of the incident photon approaches from below to the absorption edge of the target elemet, a strong resonant behavior takes place contributing to the attenuation of x-rays in matter. According to the absorption-emission model the RRS process can be represented by three steps [2]: 1) the initial state consists of an incident photon with an energy below, for example, the K threshold 2) a hole is produced in the K shell and the excited electron is ejected to an unoccupied state; an electron from a higher shell fills the vacancy and a photon is emitted 3) the final state consists of a hole in a higher shell, a scattered photon and an excited electron in the continnum or in a bound excited state.